Zielona Góra w niemieckim piśmiennictwie do roku 1945 (w ujęciu historyczno-bibliograficznym) = Zielona Góra in German literature until 1945 (historical and bibliographical perspective) - Kotlarek, Dawid (Zielona Góra: "Pro Libris" Wydawnictwo Wojewódzkiej i Miejskiej Biblioteki Publicznej w Zielonej Górze)
This publication presents an analysis of German literature concerning Zielona Góra and its surroundings until 1945. The author discusses the development of literature relating to the city - from the oldest chronicles and historical studies, through monographs, local literature, and publications on winemaking, to the local press. Particular attention is also paid to individuals associated with the Zielona Góra book community and the activities of printers, publishers, and authors. The study is historical and bibliographic in nature and consists of an analytical section and an extensive bibliography of publications concerning Zielona Góra. Source material comes primarily from the collections of the C. Norwid Provincial and Municipal Public Library in Zielona Góra, as well as other libraries and archives. The work compiles sources for research on the city's history and regional literature.
Keywords: Zielona Góra; historiografia regionalna; piśmiennictwo niemieckie; bibliografia regionalna; historia książki; prasa lokalna; winiarstwo zielonogórskie; Śląsk; drukarstwo; kultura regionalna; regional historiography; German literature; regional bibliography; book history; local press; Zielona Góra winemaking; Silesia; printing; regional culture